2012
DOI: 10.1186/1743-422x-9-86
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of vitamin D and deficiency of mannose binding lectin in dengue hemorrhagic fever

Abstract: BackgroundAltered plasma concentrations of vitamin D and mannose binding lectin (MBL), components of innate immunity, have been shown to be associated with the pathogenesis of viral infections. The objective of the present study was to find out whether plasma concentrations of MBL and vitamin D are different in patients with dengue fever (DF) and dengue hemorrhagic fever (DHF).The resultsThe plasma concentrations of vitamin D and MBL were assessed in 48 DF cases, 45 DHF cases and 20 apparently healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 36 publications
2
43
2
Order By: Relevance
“…A recent study in India compared the levels of vitamin D in patients with DF and DHF with those of healthy individuals. Alagarasu and others 30 found that patients with both DF and DHF had significantly higher 25-hydroxyvitamin D levels in their blood than the healthy controls (P 0.005 and P 0.001, respectively). Alagarasu and others 30 also found that patients with secondary DHF had significantly higher vitamin D concentrations than patients with secondary DF (P 0.05).…”
Section: Vitamin D Why Vitamin D?mentioning
confidence: 85%
See 1 more Smart Citation
“…A recent study in India compared the levels of vitamin D in patients with DF and DHF with those of healthy individuals. Alagarasu and others 30 found that patients with both DF and DHF had significantly higher 25-hydroxyvitamin D levels in their blood than the healthy controls (P 0.005 and P 0.001, respectively). Alagarasu and others 30 also found that patients with secondary DHF had significantly higher vitamin D concentrations than patients with secondary DF (P 0.05).…”
Section: Vitamin D Why Vitamin D?mentioning
confidence: 85%
“…Alagarasu and others 30 found that patients with both DF and DHF had significantly higher 25-hydroxyvitamin D levels in their blood than the healthy controls (P 0.005 and P 0.001, respectively). Alagarasu and others 30 also found that patients with secondary DHF had significantly higher vitamin D concentrations than patients with secondary DF (P 0.05). Alagarasu and others 30 speculated that this association might be related to the inducing effect of vitamin D on Fcγ-receptor expression (which enhances viral entry into cells, possibly leading to higher viral load in dengue cases with secondary infection and the development of DHF) or dendritic cell-specific intercellular adhesion molecule 3-grabbing non-integrin (DC-SIGN), the primary receptor through which the virus enters immature dendritic cells.…”
Section: Vitamin D Why Vitamin D?mentioning
confidence: 85%
“…It has been shown that vitamin D is known to suppress the replication of DENV [7]. A recent study has reported higher levels of 25-hydroxy vitamin D 3 in DENV infected patients compared to apparently healthy controls [8]. Vitamin D has been shown to upregulate the expression of DENV entry receptors, dendritic cell specific intercellular adhesion molecule-3 grabbing non integrin (DC-SIGN) and FcGRIIA [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Our study herein is the first to estimate the level of vitamin K in dengue patients. Alagarasu et al, 8 in their study, determined vitamin D 3 level in dengue patients where they found an increased level of vitamin D 3 in dengue patients. Sánchez-Valdéz et al 18 reported that administration of vitamin D 3 to the dengue patients improved overall clinical condition and reduced the duration of signs and symptoms of dengue fever.…”
Section: Discussionmentioning
confidence: 95%
“…Vitamin D 3 also reported to influence the expression of DENV receptors in immune cells. 8 Bleeding, one of the main problems experienced in dengue fever, contributes to worsening morbidity. 9 The significance of vitamin K for hemostasis is established from the fact that deficiency of vitamin K is a critical, life-threatening situation due to excessive bleeding.…”
Section: Introductionmentioning
confidence: 99%